Anomalous Discharge of Endogenous Gas at Lavinio (Rome, Italy) and the Lethal Accident of 5 September 2011. Issue 12 (3rd December 2019) - Barberi, F.; Carapezza, M. L.; Tarchini, L.; Ranaldi, M.; Ricci, T.; Gattuso, A.
Abstract: The Rome region contains several sites where endogenous gas is brought to the surface through deep reaching faults, creating locally hazardous conditions for people and animals. Lavinio is a touristic borough of Anzio (Rome Capital Metropolitan City) that hosts a country club with a swimming pool and an adjacent basement balance tank. In early September 2011, the pool and the tank had been emptied for cleaning. On 5 September, four men descended into the tank and immediately lost consciousness. On 12 August 2012, after a long coma the first person died, the second one reported permanent damage to his central nervous system, and the other two men recovered completely. Detailed geochemical investigations show that the site is affected by a huge release of endogenous gas (CO2 ≈ 96 vol.% and H2 S ≈ 4 vol.%). High soil CO2 and H2 S flux values were measured near the pool (up to 898 and 7.155 g·m −2 ·day −1, respectively), and a high CO2 concentration (23–25 vol.%) was found at 50–70 cm depth in the soil. We were able to demonstrate that gas had been transported into the balance tank from the swimming pool through two hubs connected to the lateral overflow channels of the pool. We show also that the time before the accident (60 hr), during which the balance tank had remained closed to external air, had been largely sufficient to reach indoor nearly lethal conditions (oxygen deficiency and high concentration of both CO2 and H2 S). Plain Language Summary: Rome volcanic region contains several sites where deep gas consisting mostly of carbon dioxide (CO2 ) with 1–6% of hydrogen sulfide (H2 S) is brought to the surface by faults, locally creating hazardous conditions. Lavinio is a touristic borough of Anzio (Rome province) located near the Tyrrhenian Coast. It hosts a country club with a swimming pool and an adjacent basement balance tank. In early September 2011, four men descended into the tank to clean it and immediately lost consciousness. After a nearly 1‐year coma, the first man died and the second one suffered permanent damage to his central nervous system. Immediately after the accident, we carried out detailed geochemical investigations aimed at ascertaining the accident causes. The results show that the accident occurred because of a nearly lethal gas concentration indoor the emptied balance tank. The gas had been transported into the tank through two hubs connected to the overflow channels of the pool, where we measured very high concentration of both CO2 and H2 S. Geoscientific evidence indicates that the pool has been excavated in a severe gas‐risk prone area, and it can be easily inferred that excavation works created new additional ways allowing gas to escape to the surface. Key Points: In volcanic and geothermal areas, the emission of deep gas locally creates hazardous conditions for people and animals, as at Lavinio Lavinio country club hosts a swimming pool with a basement tank, where an accident occurred on 5 September 2011 causing the death of a man Geochemical studies show that the man inhaled a nearly lethal CO2 ‐H2 S‐rich air mixture, transported from the pool into the basement tank